Not all is fair in love and war: A comprehensive study on the current legal status of inter-corporate transfer pricing taxation on sales and purchases of goods in the Philippines of a local affiliate company that has a transfer pricing agreement with its mother corporation domiciled abroad - Granado, Lorelee Margaret T. (Animo Repository, 2014)
All is fair in Love and War. As depicted in the classic Greek Mythology of The Fall of Troy. It is a popular English saying which usually means that one is allowed to do or say something that is deceitful, in order he/she can get what they want1. This saying is not applicable to taxation though, specifically in the area of Transfer Pricing. The dramatic increase in globalization of trade has also led to harmful tax practices that have resulted in tremendous losses of tax revenue for government. The most significant international tax issue emerging from globalization confronting tax administrations worldwide is transfer pricing2. Transfer Pricing is probably the most critical and complicated issue in International Taxation. It is an extremely sensitive and secretive area for all firms, especially multinational firms, and with the taxing authorities as well, as it is an avenue for the companies to avoid or evade taxes. Currently, much of the problem arise out of the lack of suppletory laws or regulations to address the deficiency in the provision of Section 50 of the National Internal Revenue Code for the Commission of Internal Revenue (CIR) to distribute, apportion, or allocate gross income or deductions between or among related organization, trade or business, if the determination that such distribution, apportionment, or allocation is necessary in order to prevent evasion of taxes or clearly reflect the income of such organization, trade or business and place the related entity in tax parity with an uncontrolled party. There is therefore a need for innovative revenue regulations that will take into account current transfer pricing regulations on intercompany sales and purchases and a modified version for the purpose of simplifying the regulative aspect of transfer pricing and subsequently, to render the effectivity and efficiency of Section 50 concrete.